RPE-specific MCT2 expression promotes cone survival in models of retinitis pigmentosa - Laurel C. Chandler; Apolonia Gardner; Constance L. Cepko (Proceedings of the National Academy of Sciences, 2025)
Retinitis pigmentosa (RP) is the most common cause of inherited retinal degeneration worldwide. It is characterized by the sequential death of rod and cone photoreceptors, the cells responsible for night and daylight vision, respectively. Although the expression of most RP genes occurs only in rods, there is a secondary degeneration of cones. One possible mechanism of cone death is metabolic dysregulation. Photoreceptors are highly metabolically active, consuming large quantities of glucose and producing substantial amounts of lactate. The retinal pigment epithelium (RPE) mediates the transport of glucose from the blood to photoreceptors and, in turn, removes lactate, which can influence the rate of consumption of glucose by the RPE. One model for metabolic dysregulation in RP suggests that following the death of rods, lactate levels are substantially diminished causing the RPE to withhold glucose, resulting in nutrient deprivation for cones. Here, we present adeno-associated viral vector-mediated delivery of monocarboxylate transporter 2 (MCT2, Slc16a7 ) into the eye, with expression limited to RPE cells, with the aim of promoting lactate uptake from the blood and encouraging the passage of glucose to cones. We demonstrate prolonged survival and function of cones in rat and mouse RP models, revealing a possible gene-agnostic therapy for preserving vision in RP. We also present the use of fluorescence lifetime imaging-based biosensors for lactate and glucose within the eye. Using this technology, we show changes to lactate and glucose levels within MCT2-expressing RPE, suggesting that cone survival is impacted by changes in RPE metabolism.